PENGARUH MODEL PEMBELAJARAN MASTER TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA - Lafita Rahmi (Departemen Matematika, 2018)
One of the cognitive abilities that is expected to be possessed by students in learning mathematics is understanding of mathematical concepts. However, it seen that the students’ understanding of mathematical concepts is still low, so it needs to be improved. One of learning models to improve the students’ understanding of mathematical concepts is MASTER learning model. Type of this research is quasy experiment with static group design, and also involved two sample classes. The experiment class study by applying MASTER learning model and control class study by applying conventional learning. The data were collected using a mathematical concepts comprehension test, and then analyzed using t test. Based on the results of data analysis, at significant level α = 0,05, obtained P-value = 0,028. P-value ˂ α, so H0 is refused. Hence, it can be concluded that the understanding of mathematical concepts of students that study by MASTER learning model is better than that study by conventional learning. Keywords –Conventional Learning, MASTER Learning Model, Understanding of Mathematical Concept